Availability of feed sources and nutritional status of Hariana cattle in different seasons in the breeding tract. Issue 6 (3rd July 2021) - Singh, Man; Lathwal, S. S.; Kotresh Prasad, C.; Dey, Deepak; Gupta, Anuradha; Saini, Mayamitta; Lathwal, Indu; Sharma, Bharti; Kumar, Muneendra; Sharma, Vijay
ABSTRACT: The study was conducted to assess the availability of feed sources and nutritional status of Hariana cattle breed during different season in its breeding tract. The structed interview schedule was prepared to collect the information from 240 dairy farmers and the samples of available feed and fodder were collected during different season for proximate analysis. The results revealed that the fodder availibility varies according to season. The available green fodders were maize and jowar during rainy; berseem and oats during winter. The intake of nutrients were compared with requirements of Hariana cattle to find out the nutritional status during different season. The results revealed that the animals were underfed in different seasons. Dry matter intake (DMI) was deficit in all seasons; deficiency of DMI (%) was 21.46, 13.84 and 8.60 during summer, winter and rainy respectively. Total digestible nutrient intake was in excess during rainy and winter season and deficit during summer. Crude protein intake was in excess during winter; deficit in rainy and summer. The intake of Ca and P was less as compared to requirements. The information from the present study might be useful for formulation of balanced ration for Hariana breed of cattle.